2016
DOI: 10.2298/sarh1608384i
|View full text |Cite
|
Sign up to set email alerts
|

Useful histological findings in incisional biopsies of oral squamous cell carcinoma

Abstract: This study suggests that incisional biopsies may be useful and significant as they can show histopathological variables that are important to classify oral squamous cell carcinomas into low grade and high grade according to Bryne’s score, which was used in this study. Thus, more representative biopsies might be useful to achieve this and allow a more accurate planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Previous data showed that the development of a necrotic core in cancer patients is correlated with increased tumor size and poor prognosis, such as the emergence of chemoresistance [ 6 , 7 ]. One of the unique clinicopathological characteristics of OSCC tumors is that necrosis is observed only in limited cases [ 8 , 9 ]. Therefore, in vivo animal models resulting in very little or no tumor necrosis may be useful for OSCC chemotherapy screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous data showed that the development of a necrotic core in cancer patients is correlated with increased tumor size and poor prognosis, such as the emergence of chemoresistance [ 6 , 7 ]. One of the unique clinicopathological characteristics of OSCC tumors is that necrosis is observed only in limited cases [ 8 , 9 ]. Therefore, in vivo animal models resulting in very little or no tumor necrosis may be useful for OSCC chemotherapy screening.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, cell death via necrosis is not preferred as an anticancer strategy due to the consequent inflammatory response [ 7 ]. OSCC has different clinical characteristics from other solid tumors, one of which is that necrosis is observed in only about 10% of cases with a high grade of malignancy [ 8 ]. Also, when the clinicopathological features of 346 cases of OSCC were investigated, 76% were smaller than 4 cm, and only 6% were bigger than 6 cm [ 9 ].…”
Section: Introductionmentioning
confidence: 99%